2012
DOI: 10.1177/1756287212441961
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer in the second trimester of pregnancy: tough decisions. A case report with review of the literature

Abstract: We report a rare case of a patient presenting with a nonmuscle invasive papillomatosis transitional cell carcinoma of the bladder in the second trimester of pregnancy. We describe the management dilemmas encountered and the challenging treatment option selected to optimize outcome for the patient and infant. Close collaboration between urologists, obstetricians and medical colleagues is needed for optimal, safe and effective management of bladder tumours during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…In our case, however, symptoms appeared during third trimester and persisted during pregnancy. Although during pregnancy the symptoms of the patient generally disappear due to endocrinal reasons and decidualization [4] , in our case the decidualization and the mechanical trauma due to stromal development in the bladder nodule might be themselves have triggered the symptoms of hematuria and dysuria.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In our case, however, symptoms appeared during third trimester and persisted during pregnancy. Although during pregnancy the symptoms of the patient generally disappear due to endocrinal reasons and decidualization [4] , in our case the decidualization and the mechanical trauma due to stromal development in the bladder nodule might be themselves have triggered the symptoms of hematuria and dysuria.…”
Section: Discussionmentioning
confidence: 57%
“…The urinary tract endometriosis is observed in 1–2% of the patients and in 90% of these cases there are endometriotic nodules in the bladder [1] , [2] . Patients with bladder endometriosis may have many non-specific symptoms that make timely diagnosis difficult [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of biopsy before tumor resection will not alter management protocol even in pregnancy as suggested in a report where a review of literature failed to find any evidence that pregnancy has deleterious effects on the incidence or clinical course of malignancy compared with that in nonpregnant women of reproductive age, except in the case of malignant melanoma [22]. By extension, this suggests that pregnancy should not alter management protocol in any way be it benign or malignant and as such every tumor should be treated in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…In our case and in most other cases where bladder tumor was found to co-exist with pregnancy, Transurethral resection of the tumor was the primary treatment regardless of the trimester and treatment was never delayed due to pregnancy. A review of different literature has shown the safety of Transurethral resection of bladder tumor under regional or general anaesthesia at any time during pregnancy [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…6,11 Certainly, gold standard in the diagnosis of bladder tumor is cystoscopy performed under local anesthesia even if the patient is pregnant. 12 Although it is known that since most of the bladder tumors diagnosed by cystoscopy are superficial, they can be effectively treated with transurethral resection at any time during pregnancy however, some studies report that treatment can be delayed until post partum period particularly in low grade bladder tumors. 6,13 Resection of bladder tumor by using bipolar resectoscope during pregnancy did not cause any intraoperative or postoperative fetal repercussions.…”
Section: Discussionmentioning
confidence: 99%